Caprine lung diseases and causal bacteria - Ferdausi, T; Haider, MG; Alam, KJ; Baki, MA; Hossain, MM (Bangladesh Veterinarian, 2010)
Pathological conditions in lungs of slaughtered goats were studied. Sixty lungs were examined and tissue samples and swabs obtained for histopathology and bacterial isolation, respectively. The prevalence of lung diseases was 58.3% (n=35). Gross lesions were categorized into: (a) haemorrhage and congestion 25% (b) emphysema 21.7% (c) hepatization 3.3% and (d) granulomatous nodules about 1 mm diameter 8.3%. On histopathological examination, 10 types of lesions were found: (a) bronchitis 6.7%, (b) small cell anaplastic carcinoma 3.3%, (c) pneumonia 6.7%, (d) interstitial pneumonia 15%, (e) emphysema 6.7%, (f) bronchopneumonia 3.3%, (g) purulent pneumonia 5%, (h) haemorrhagic pneumonia 3.3%, (i) pulmonary adenomatosis 1.7% and (j) no lesions 6.7%. Pasteurella sp. (11.7%), Escherichia coli (E. coli; 6.7%), Staphylococcus sp. (36.7%) and Bacillus sp. (3.3%) were isolated from the lungs. Pasteurella sp. was found in haemorrhagic pneumonia, interstitial pneumonia, small cell anaplastic carcinoma and bronchitis, followed by Bacillus sp. in haemorrhagic pneumonia, E. coli in interstitial pneumonia and pulmonary adenomatosis and Staphylococcus sp. from emphysema, bronchopneumonia, pneumonia, bronchitis and purulent pneumonia. DOI: 10.3329/bvet.v25i1.4613 Bangl. vet. 2008. Vol. 25, No. 1, 9-16